Managing paper trails after Windrush: Migration, documents and bureaucracy. Issue 2 (1st December 2019) - Tuckett, Anna
Abstract : Stories of those who were victims of the Windrush scandal are characterised by tales of long-lost documents and urgent quests to procure paperwork – maternity certificates, payslips, dental records, school reports – that would attest to a lifetime spent in the United Kingdom. The so-called Windrush generation came to need this paperwork because, although unbeknown to most, the 1971 Immigration Act demanded that from 1973, all migrants must document their 'legal' presence in the UK. It was, however, only from 2014 – because of changes in legislation – that now retirement-age Commonwealth citizens, most of whom had migrated to the United Kingdom as children, found themselves facing deportation back to countries that many had not visited for decades (for a historical account of the legislation and politics that led to the Windrush scandal, see Olusoga 2019). The 2014 Immigration Act deleted a key clause of the 1999 legislation that had provided long-standing Commonwealth residents with protection from enforced removal (Taylor 2018). Some of those affected by this updated legislation report that they believed themselves to be legitimate citizens of the British state and therefore did not need to prove their right to be resident through such documentation (for case studies, see Gentleman 2019). In this case, as well as in common-sense thought more generally, documents and paperwork are understood to hold the 'truth'. Uncover it and their holder's rightful status will be triumphantly revealed. As such, documents are imagined to act as unambiguous mechanisms of inclusion, their absence therefore denoting the exact opposite.